THU0025 Il-6 trans-signaling causes accelerated atherosclerosis in disease prone animals. (15th June 2017) - Davies, R; Jin, HS; Sime, K; Williams, JO; Thompson, CR; Jones, GW; Allen-Redpath, K; Jones, SA; Hughes, TR; Rose-John, S; Williams, AS; Choy, EHS
Abstract : Background: Cardiovascular (CV) disease is a major cause of mortality in patients with rheumatoid arthritis (RA). CV risk is increased early in the disease course. Subclinical inflammation and dyslipidaemia are often seen in RA before patients become symptomatic, suggesting the presence of subclinical CV disease. Inflammation, as measured by acute phase reactants, is associated with CV disease in RA. Interleukin (IL)-6 is a major driver of the acute phase response in RA. Notably, systemic elevations in inflammatory cytokines including IL-6 correlate with CV risk. Importantly, IL-6 regulates both immune homeostasis and inflammatory processes linked with chronic disease progression. Control of these processes is regulated by two modes of IL-6 signaling; classical IL-6 receptor signaling and IL-6 trans-signaling. Cellular responses controlled by IL-6 trans-signaling are mediated via soluble IL-6 receptor (sIL-6R) and is widely considered to promote deleterious pro-inflammatory outcomes [1]. We hypothesize that atherosclerosis may predate diagnosis of RA, and is accelerated by IL-6 trans-signaling during active arthritis. Here, we investigate this hypothesis using the established ApoE-deficient ( apoE -/- ) mouse model of atherosclerosis. Objectives: To examine the effect of IL-6 classical and trans-signaling on atherosclerosis by administering IL-6 or Hyper-IL-6 (a IL-6: sIL-6R fusion protein) to apoE -/- mice. Methods: Male apoE -/- mice were fed a high-fat diet for 8 weeks starting at 8 weeks of age. Mice were divided into 4 groups. Group 1 received IL-6 (160 ng twice weekly, delivered i.p.), and Group 2 and 3 received Hyper-IL-6 (500 ng and 1 μg delivered i.p. twice weekly) for 8 weeks. Group 4 received PBS twice weekly for 8 weeks. Serial transverse 7 um brachiocephalic artery cross-sections were cut and stained with haematoxylin and oil red-O. Lesion size was determined by computer-assisted morphometry, using Image J on stained sections. Brachiocephalic plaque size in mice treated with PBS, IL-6 and Hyper-IL6 were compared using ANOVA and post-hoc Tukey t test. Results: Mice treated with Hyper-IL-6 1μg had significantly larger brachiocephalic plaques (mean plaque area 0.73±0.04 mm 2 ) than those administered PBS (0.018±0.01 mm 2, p <0.001), and IL-6 (0.033±0.017 mm 2, p =0.015; Fig.1 A). Similarly, mice administered Hyper-IL-6 [1μg] had a significantly higher percentage of the brachiocephalic artery occupied by plaques (45.3±18.1%) compared to those administered PBS (10.38±6.7%, p <0.001) or IL-6 (20.1±10.2%, p =0.002) (Fig.1 B). Mice administered Hyper-IL-6 [0.5μg] had significantly higher percentage plaque (27.7±16.2%) than PBS administered mice, p =0.015. There was no significant difference in total cholesterol, HDL, LDL, triglycerides, free fatty acids or cholesterol:HDL ratio between the groups. Conclusions: IL-6 trans-signaling leads to accelerated atherosclerosis in disease susceptible animals. This effect is independent of changes in serum lipid profiles. References: Rose-John S. IL-6 Trans-Signaling via the Soluble IL-6 Receptor: Importance for the Pro-Inflammatory Activities of IL-6. Int. J. Biol. Sci. 2012;8(9):1237–1247. Acknowledgements: This work was funded by Arthritis Research UK, grant number 20760. Disclosure of Interest: None declared